Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Solve

$$\frac{4}{x+1}+\frac{2}{x-2} \leq 3$$

I must be making a very stupid mistake somewhere ... been stuck on this for 1hr+ or even more ...

enter image description here

share|improve this question

4 Answers 4

up vote 3 down vote accepted

$$ \begin{eqnarray} \frac{2(x-1)}{(x+1)(x-2)} &\leq& 1 \implies \\ \frac{2(x-1)}{(x+1)(x-2)} - 1 &\leq& 0 \\ \frac{(2x-2)-(x+1)(x-2)}{(x+1)(x-2)} &\leq& 0 \\ \frac{(2x-2)-(x^2-x-2)}{(x+1)(x-2)} &\leq& 0 \\ \frac{(2x-2)-(x^2-x-2)}{(x+1)(x-2)} &\leq& 0 \\ \frac{-(x^2-3x)}{(x+1)(x-2)} &\leq& 0 \\ \frac{-(x^2-3x)}{(x+1)(x-2)} &\leq& 0 \implies \\ \frac{x(x-3)}{(x+1)(x-2)} &\geq& 0 \\ \end{eqnarray} $$ If we look at this on a number line, first note that for $x$ large enough, the LHS is positive. Next, note that the LHS changes sign each time $x$ crosses a root of one of the terms in the top or bottom, i.e. when $x \in \{-1,0,2,3\}$. Thus the LHS is nonnegative for $x \in (-\infty,-1) \cup [0,2) \cup [3,\infty)$.

share|improve this answer

You made no mistake. Note however that you need to exclude the cases $x=-1, x=2$ by hand because your initial inequality is not defined for such $x$.

Then you have to see that

$$x^4 - 4 x^3 + x^2 + 6=(x-3) (x-2) x (x+1)$$

Now look at the plot and you should know what to do:

enter image description here

share|improve this answer

@jiewmeng: As Listing pointed the graph tells you what you want, however, the below image would assist you. I made it as you posted your question:

enter image description here

share|improve this answer
    
Nice table! What did you use to make it? –  amWhy Mar 3 '13 at 18:05
    
@amWhy: Office word. –  Babak S. Mar 3 '13 at 18:07
    
Did you save as an image and import? Or did you scan, and import the scanned image? –  amWhy Mar 3 '13 at 18:08
    
@amWhy: Image and then import. I convert it to pdf and then import. –  Babak S. Mar 3 '13 at 18:16

One solution is given below. Another one, very close in spirit to your attempt, is given in a comment at the end.

It turns out that the numbers fit together perfectly! Rewrite our inequality as $$\frac{4}{x+1}-4 +\frac{2}{x-2}-1 \le 0.$$ This simplifies to $$-\frac{4x}{x+1}+\frac{x}{x-2} \le 0.$$ The problem now breaks up into two natural cases.

Case (i): $x\ge 0$. Here our inequality is equivalent to $$\frac{1}{x-2}\le \frac{4}{x+1}.$$ For $x >2$ this can be rewritten as $4(x-2)\ge x+1$, giving $x\ge 3$. For $0\le x<2$, we get in a similar way $x \le 3$, which holds automatically. We have obtained the intervals $[3,\infty)$ and $[0,2)$.

Case (ii): $x<0$. Here our inequality is equivalent to $$\frac{1}{x-2}\ge \frac{4}{x+1}.$$ This is automatically false if $-1<x<0$, since the left side is negative and the right side is not. When $x<-1$, the inequality is equivalent to $x+1 \ge 4(x-2)$, which holds. This gives us the additional interval $(-\infty, -1)$.

Comment: In order to solve the inequality, you used the nice strategy of multiplying by $(x+1)^2(x-2)^2$. When we do that, we have to note that $x\ne -1, 2$. Minor point. The major point is that you should "multiply out" only when you have to. Multiplying out tends to create a mess. If you keep the common factors of the two sides separated out, your calculation pushes through smoothly. Starting from your $$2(x-1)(x+1)(x-2)\le (x+1)^2(x-2)^2,$$ we obtain $$(x+1)(x-2)\left[(x+1)(x-2)-2(x-1)\right]\ge 0,$$ which simplifies to $$(x+1)(x-2)(x^2-3x) \ge 0.$$ Since $x^2-3x=x(x-3)$, the analysis becomes routine.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.